Does User-Centered Design (UCD) matter? perspectives of Malaysian IT organizations - Hussein, Idyawati; Mahmud, Murni; Md Tap, Abu Osman; Laura, Jack (Faculty of Computing, Universiti Teknologi Malaysia, 2013)
In the field of Human-Computer Interaction (HCI), user needs are recognized to be the most crucial component in designing towards usability, hence user experience (UX). This paper explores the most valued component at the earliest phases of design and appreciation of end users among information technology (IT) personnel with different roles at organisations in Malaysia. The organisations are divided into three (3) categories; government agencies, government-link company (GLC), private company. Eighty four (84) personnel are surveyed using a semi-structured questionnaire. The study investigates the gap of awareness in User-Centered Design (UCD) and most important values during IT development process in the organisations. The result points that little evidence is available on the level of user involvement during the design process even thou many respondents believe that user should be the centre of the design process. There is a gap in the International usability standards currently embedded at the national and organisational level at all organisations.